The Palgrave Handbook of African Traditional Religion - Aderibigbe, Ibigbolade S.; Falola, Toyin (Palgrave Macmillan, 2022)
The Palgrave Handbook of African Traditional Religion interrogates and presents robust and comprehensive contributions from interdisciplinary experts and scholars. Offering a range of perspectives and opinions through the prism of understanding the past about African Traditional religions and, more importantly, capturing their dynamics in the present and projecting their sustainability and relevance for the future, this volume is an essential resource for knowledge and understanding of African Traditional religions in the global space of religious traditions.
paid
Keywords: History / Africa / General; Political Science / General; Political Science / World / African; Religion / Comparative Religion; Religion / General; Social Science / Anthropology / Cultural & Social; Social Science / General